Caracterización de la regeneración natural del bosque de la Estación Científica Kutukú, parroquia Sevilla Don Bosco, cantón Macas - Paucar Estévez, Maritza Amelia (2017)
This research was done in a 10-hectare area in a primary forest ecosystem. This area belonging to the Kutukú-EBK Biological Station, located in the Sevilla Don Bosco, in Macas city, province of Morona Santiago, in order to determine the floristic composition and characterize the Natural regeneration, by studying the categories: “brinzales and latizales.” The field data obtained were made in the Permanent Production Plot (PPP), with an area of 1 ha, which was established in 2016. For the brinzaled, the simple random sampling method was applied, starting from The Division of the PPP in subplots of 10 x 10 m. In this case, the individuals were from 30 cm in height. For latizales, a forest census was applied, to get this data, the total height of the individual and the Diameter to the Height of the Chest (DHC) from 1 cm was taken. In this case, we evaluated the richness, diversity, abundance of the species and the natural regeneration of the forest. For individuals with a DHC mayor at 10 cm, the following variables were calculated: volume, forest biomass, amount of carbon and CO2 stored. Then the results are 31 families, 19 genera, 86 species and 3423 individuals per hectare, containing 33.74 m3 of wood were registered, demonstrating the high potential for natural regeneration. The family with the highest prevalence is Euphorbiaceae, whose most representative species are Mabea speciosa Müll. Arg. and Acalypha cuneata Poepp. & Endel.